Transforming Islamic Finance through Leadership: K.H. Ma'ruf Amin’s Contribution to Inclusive Financial Institutions in the Digital Era - Hari Risky Syahputra; Muhammad Firdaus; Dida Novandika (J-MD Jurnal Manajemen Dakwah, 2025)
This study examines the strategic leadership of Prof. Dr. K.H. Ma’ruf Amin in shaping the foundations of Islamic financial institutions in Indonesia. As a leading Islamic scholar and former Chairman of the Indonesian Ulema Council (MUI), Prof. Amin played a pivotal role in initiating and legitimizing fatwas that became the legal basis for the operations of Islamic banking and financial institutions. His leadership within the National Sharia Council (DSN-MUI) ensured the consistent application of Sharia principles across financial products and services, strengthening institutional trust and regulatory compliance. Using a qualitative descriptive approach, this research explores his ideas, policies, and leadership style in promoting the integration of Islamic finance into the national financial framework. The novelty of this study lies in its focus on the intersection between religious leadership and institutional transformation within the context of Indonesia’s digital-era Islamic finance development a perspective rarely addressed in existing literature. The findings indicate that Prof. Amin’s leadership model has been crucial in mainstreaming Islamic finance as part of Indonesia’s national economic system. The implications suggest that his approach provides a replicable framework for other Muslim-majority nations aiming to harmonize religious authority, policy-making, and financial innovation in advancing inclusive and ethical financial ecosystems.